School leadership - Ravit, Amir (IJRDO - Journal of Applied Management Science, 2016)
In today's world we are engaged in endless preparation of lists of almost everything weknow. We already lists of the richest people in the world, the most numerous downloadsfrom the Internet, the most beloved movies, a thousand and one things that must beenough to do, see or visit during life, and so on and so on! Education is no different -there are lists of characteristics of effective schools, effective teachers, six ways tomanage the behavior of students, the ten main lessons learned regarding school.improvement and the key characteristics of school leaders successfulIndeed, often these lists are useful summaries of knowledge at our disposal, but should betreated with caution Hrsimti logic, "as Roland Barthes called" the way of thinking 20years ago (Barth 1990: 38). This is, in part, because such lists can be used nucleic Whilethinking, but not all provide us with sufficient illumination or deepening our knowledgeas we would like. Otherwise, today there are already so many lists on education and!leadership to the need for preparation of a list of listsSociety for Research on education (American Educational Research Association), forexample, invited a team of researchers form the totality of what we know about schoolleadership success (Leithwood & Riehl, 2003). The result Lotsh and was developedfurther and become known as Seven strong claims about the verification test schoolleadership ("Seven convincing case about school leadership succeeds in" Leithwood et al.2006). Around the same time the value of the National Institute for School Leadership(NCSL), England synthesis of all the research on leadership committed five years ofactive research and knowledge production. The Institute gathered together commissionedresearch findings, studies of the area and the conclusions derived seminars and thinktanks, and produced an overview of recent knowledge on the subject of school leadership.